1999
DOI: 10.1098/rstb.1999.0471
|View full text |Cite
|
Sign up to set email alerts
|

Cellular mechanisms of brain energy metabolism and their relevance to functional brain imaging

Abstract: Despite striking advances in functional brain imaging, the cellular and molecular mechanisms that underlie the signals detected by these techniques are still largely unknown. The basic physiological principle of functional imaging is represented by the tight coupling existing between neuronal activity and the associated local increase in both blood £ow and energy metabolism. Positron emission tomography (PET) signals detect blood £ow, oxygen consumption and glucose use associated with neuronal activity; the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
466
1
15

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 670 publications
(498 citation statements)
references
References 56 publications
16
466
1
15
Order By: Relevance
“…Magistretti et al 12 assumed a "lactate shuttle" model, where glucose was transformed by the astrocytes into lactate and diffused from astrocytes to neurons using the monocarboxylate transporters (MCTs). Tsukaguchi et al 13 found that AQP9 permeability to lactate increased four-fold when the pH decreased to 5.5.…”
Section: Discussionmentioning
confidence: 99%
“…Magistretti et al 12 assumed a "lactate shuttle" model, where glucose was transformed by the astrocytes into lactate and diffused from astrocytes to neurons using the monocarboxylate transporters (MCTs). Tsukaguchi et al 13 found that AQP9 permeability to lactate increased four-fold when the pH decreased to 5.5.…”
Section: Discussionmentioning
confidence: 99%
“…This view is still generally held to be true (Magistretti & Pellerin, 1999;Logothetis et al, 2001). The issue of how to translate baseline and scaling effects in fMRI is still poorly understood.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, methods such as structural equation modeling (SEM (McIntosh & Gonzalez-Lima, 1992;McIntosh & Gonzalez-Lima, 1994) and dynamic causal modeling (DCM; do not take synaptic inhibition and energetic consequences of modulatory neurotransmitter effects into account. For example, how synaptic inhibition affects local blood flow (fMRI signal) is not well understood (Jueptner & Weiller, 1995;Magistretti & Pellerin, 1999;Logothetis et al, 2001;Caesar et al, 2003). Because of this, a positive connection weight can not necessarily be interpreted as an excitatory underlying connection.…”
Section: Introductionmentioning
confidence: 99%
“…The water protons in the vessels and surrounding tissue are affected by these changes in the magnetic field and this is detected as changes in the signal intensity of T* 2 -weighted MR images [Ogawa et al, 1990[Ogawa et al, , 1992[Ogawa et al, , 1998]. However, the mechanism behind the coupling between neuronal activity and changes in HbR content is still a matter of debate [see, e.g., Jueptner and Weiller, 1995;Magistretti and Pellerin, 1999;and Villringer, 1999, for a general discussion on this topic, Buxton and Frank, 1997;Hyder et al, 1998, for biophysical models of the relationship between blood flow and HbR, Buxton et al, 1998;Hoge et al, 1999a, for models of the coupling between blood flow and BOLD signal, Woolsey et al, 1996;Malonek and Grinvald, 1996;Malonek et al, 1997;Yang et al, 1997;Vanzetta and Grinvald, 1999;Silva et al, 1999, andSilva et al, 2000, for detailed empirical characterization of this coupling].…”
Section: The Bold Signal Responsementioning
confidence: 99%